What the landscape can tell: An integrative stratigraphic prospection approach to localize a Black Death mass grave in Erfurt/Central Germany - Michael Hein; Nik Usmar; Annabell Engel; Johannes Rabiger-Völlmer; Johannes Schmidt; Matthias Silbermann; Marco Pohle; Iris Nießen; Martin Offermann; Lukas Werther; Birgit Schneider; Christian Tannhäuser; et al. (PLoS ONE, 2026)
The Black Death pandemic (1346–53 AD) caused a 30–50% population decline across Europe. For the city of Erfurt in Thuringia, substantial human losses and corresponding mass graves are well-documented in historical archives. The aim of our study is to localize these mass graves in the nearby deserted village of Neuses in order to validate the written sources and to obtain skeletal remains for future anthropological and archeogenetic analyses. Here we present our integrative approach of historical research and minimally-invasive stratigraphic and geophysical prospection. Within the area of interest, narrowed down by historical accounts and GIS implementations, we applied percussion coring and electrical resistivity tomography (ERT). Coupled geophysical and coring sections help elucidate the late Quaternary sedimentary processes as an essential natural background for more detailed geoarcheological prospections. They allow to designate two distinct soil zones with consistent stratigraphical and pedogenic sequences: (1) a Chernozem zone and (2) a Black Floodplain Soil (humic fluvisol) zone. The distribution and extent of these zones co-determined the internal structure of the former village Neuses and the positioning of the presumed associated Black Death mass graves. Our approach enables a preliminary reconstruction of the medieval subsurface architecture, despite large-scale 20 th century ground modification. We identified a belowground pit structure, visible in both, the borehole sequences and ERT sections. Recovered bones have been AMS radiocarbon-dated to the 14 th century AD. Since confirmed and precisely-dated locations of Black Death mass graves are rare in Europe and are commonly found by chance during construction works, our systematic discovery of a possible plague pit may help to advance the research on the origin, spread and evolution of the Yersinia pestis pathogen throughout this pandemic as well as on societal coping mechanisms during epidemic outbreaks. Furthermore, our combination of methods holds the potential to successfully resolve the mapping of similarly demanding sites for archeological and forensic investigations.